Handling handles. Part II. Stratification and data analysis - Bargheer, T.; Caetano, J.; Fleury, T.; Komatsu, S.; Vieira, P. [UNESP] (Springer Nature, 2018)
In a previous work [1], we proposed an integrability setup for computing nonplanar corrections to correlation functions in N= 4 super-Yang-Mills theory at any value of the coupling constant. The procedure consists of drawing all possible tree-level graphs on a Riemann surface of given genus, completing each graph to a triangulation, inserting a hexagon form factor into each face, and summing over a complete set of states on each edge of the triangulation. The summation over graphs can be interpreted as a quantization of the string moduli space integration. The quantization requires a careful treatment of the moduli space boundaries, which is realized by subtracting degenerate Riemann surfaces; this procedure is called stratification. In this work, we precisely formulate our proposal and perform several perturbative checks. These checks require hitherto unknown multi-particle mirror contributions at one loop, which we also compute.
Keywords: 1/N Expansion; AdS-CFT Correspondence; Integrable Field Theories; Supersymmetric Gauge Theory